2013
DOI: 10.1111/jre.12060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone therapy on autogenous bone graft healing in calvarial defects: a histologic and histometric study in rats

Abstract: Ozone therapy enhances new bone formation by autogenous bone graft in the rat calvarial defect model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 33 publications
1
49
0
6
Order By: Relevance
“…Ozone application was performed with a ozone genarator. They reported that ozone therapy increased osteoblast numbers and total bone area and bone formation in autogenous bone grafts in the rat calvarial defect model 20) . Erdemci et al 21) evaluated effect of the systemic and topical ozone administration on alveolar bone healing following tooth extraction in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone application was performed with a ozone genarator. They reported that ozone therapy increased osteoblast numbers and total bone area and bone formation in autogenous bone grafts in the rat calvarial defect model 20) . Erdemci et al 21) evaluated effect of the systemic and topical ozone administration on alveolar bone healing following tooth extraction in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Topical ozone therapy was continued for five days to improve knee infection. After 20 months of follow-up, the bone and soft tissues showed complete recovery, and the patient was able to walk (25 (31) showed that ozone therapy is effective in bone healing in animal models. In an experimental study from Turkey, the researchers evaluated the adjunctive therapeutic effects of hyperbaric oxygen and ozonized oxygen in 48 male Sprague-Dawley rats.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…They concluded that postoperative long-term systemic ozone application can accelerate alveolar bone healing following extraction [38]. Ozdemir H, et al evaluated the effect of ozone therapy on autogenous bone graft in calvarial defects [39]. They concluded that ozone therapy provided to new bone formation with an autogenous bone graft in the rat calvarial defect model.…”
Section: Discussionmentioning
confidence: 99%